Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumen Pada Hotel Griya Sunset Kuta - Gede Mahendra, I Komang (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of the quality of service that consists of physical evidence, reliability, responsiveness, assurance and empathy towards customer satisfaction at Hotel Griya Sunset Kuta. This study used a qualitative research using surveys and questionnaires to 115 Sunset Kuta Puri hotel visitors. The data analysis technique used in this study is multiple linear regression analysis. It was found that the variable quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy simultaneously have an influence on customer satisfaction in the hotel Griya Sunset Kuta and the variable quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy partially positive and significant effect on customer satisfaction in the hotel Griya Sunset Kuta. Keywords : Service Quality, Customer Satisfaction